Aspectos referentes ao estupro, às vítimas e aos agressores segundo processos-crime em Uberlândia-MG - Resende, Tatiana Carneiro de (2008)
This was an epidemic study about observations of rape in Uberlândia, from data extracted from the crime lawsuits of Abelardo Pena Court from 1960 to 2005. Out of the 240 cases, the major number of victims were 10 to 19 years old (198; 82,8%), single (84; 35%), white (137; 60,4%), low educated (204; 94,4%) and maids (105; 86%). The aggressors were between 20 and 29 years old (103; 43,8%), single (129; 55,1%), bricklayers (54; 24,5%) and low educated (160; 77,2%). The majority of the aggressors were the victims boyfriends (36,5%) and most of the rapes happened at the victims house (80; 33,8%). The most common injuries were in the himen (127; 81,4%) and the anatomical area most injured were the genitals (131; 85,6%).This kind of violence represents a big challenge to society, demanding integrated actions between Justice, Educational , Social and Health programs working together with society. Notifications must be done, because, otherwise, subsides won t be given by the government to create mechanisms to fight rape.